Myofascial Release for Chronic Low Back Pain: A Systematic Review and Meta-Analysis - Wu, Zugui; Wang, Yi; Ye, Xiangling; Chen, Zehua; Zhou, Rui; Ye, Zixuan; Huang, Jinyou; Zhu, Yue; Chen, Guocai; Xu, Xuemeng (Frontiers in Medicine, 2021)
Background: Chronic low back pain (CLBP) is one of the most common musculoskeletal diseases in the elderly, which has a severe impact on the health of the elderly. However, CLBP treatment is very challenging, and more effective treatment methods are needed. Myofascial release may be an effective therapy for the management of chronic musculoskeletal pain. It is widely used clinically to treat CLBP, but its clinical efficacy is still controversial. Objective: This study aims to systematically evaluate the effectiveness of myofascial release for patients with CLBP. Methods: We selected PubMed, Cochrane Library, EMBASE database, and Web of Science database articles published until April 5, 2021. Randomized controlled trials (RCTs) of myofascial release for CLBP were included. Outcome measures included pain, physical function, quality of life, balance function, pain pressure-threshold, trunk mobility, and mental health. For each outcome, Standardized mean differences (SMD) or mean differences (MD) and 95% confidence intervals (CIs) were calculated. Results: Eight RCTs (n=375) were included based on inclusion and exclusion criteria. The meta-analysis showed that the overall efficacy of myofascial release for CLBP was significant, including two aspects: pain [SMD = -0.37, 95% CI (-0.67, -0.08), I2 = 46%, P = 0.01] and physical function [SMD = -0.43, 95% CI (-0.75, -0.12), I2 = 44%, P = 0.007]. However, myofascial release did not significantly improve quality of life [SMD = 0.13, 95% CI (-0.38, 0.64), I2 = 53%, P = 0.62], balance function [SMD = 0.58, 95% CI (-0.49, 1.64), I2 = 82%, P = 0.29], pain pressure-threshold [SMD = 0.03,95% CI (-0.75, 0.69), I2 = 73%, P = 0.93], trunk mobility [SMD = 1.02, 95% CI (-0.09, 2.13), I2= 92%, P = 0.07] and mental health [SMD = -0.06, 95% CI (-0.83, 0.71), I2 = 73%, P = 0.88]. Conclusions: In this study, we systematically reviewed and quantified the efficacy of myofascial release in treating CLBP. The meta-analysis results showed that myofascial release significantly improved pain and physical function in patients with CLBP but had no significant effects on balance function, pain pressure-threshold, trunk mobility, mental health, and quality of life.